Geophysical explorations by resistivity and induced polarization methods for the copper deposit, South Khorasan, Iran; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 333, № 3 - Shirazy A. Adel; Hezarkhani A. Ardeshir; Shirazy A. Aref; Timkin T. V. Timothy Vasilyevich; Voroshilov V. G. Valery Gavrilovich (2022, 2022)
Заглавие с титульного листа